Plan de mejoramiento del proceso de aprobación de fletamentos solicitados mediante el Sistema Integrado de Tráfico y Transporte Marítimo Internacional SITMAR, a los buques que arriban a los puertos Marítimos de Santa Marta. (2023)
The purpose of this work is the design and implementation of an improvement plan that contributes to the optimization and improvement of the process of approval and verification of charters of the General Maritime Authority DIMAR, requested through the Integrated System of Traffic and International Maritime Transport SITMAR, of ships arriving at the different maritime ports of the city of Santa Marta under this modality. The International Maritime Organization (IMO) establishes in its Convention on the Facilitation of International Maritime Traffic (FAL) that shipping agencies are an essential part of the maritime traffic facilitation system. It also establishes that they are key to facilitating international trade. As important points it mentions that, for the exchange of information between port authorities, ship masters and shipping agencies, an established regulation is applied, in order to contribute to the efficiency of the movement of ships and their operations in the different maritime ports (Convention on Facilitation of International Maritime Traffic, 1965). For the design and implementation of the improvement plan, a review of the regulations established by the maritime authority for the approval and verification of charters was carried out in order to make a comparison with the current process, from the time the process is requested by the shipping agency until it is approved and verified. With the development of all the proposed activities, it was possible to contribute to the improvement of the process, optimizing the process of verification and approval of charters, taking into account the regulations stipulated for the process, avoiding delays and charges in the SITMAR due to the control and daily monitoring, as a result, the due compliance by the shipping agencies in the documentation and times according to the regulations was obtained. Due to the great importance of DIMAR as the Colombian maritime authority and its role as a coordinating entity within the port operations and the physical security of the same, it allowed the acquisition and adoption of new knowledge, in real spaces that forge the character as a future professional in this matter.